Subcontracting Realtionships in Indonesian Manufacturing Firms - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
The subcontracting of production, once managerially seen as "more trouble them it was worth", has recently been experiencing a revived interest as a rich territory of studies. This paper covers various relevant issues in subcontracting relationships between big and small enterprises, such as the advantages and disadvantages of the relations, perceived dependence and perceived satisfaction of the subcontractors toward their respective relationships with the contractors. My findings show that subcontracting relationships help accommodate the growth of the subcontractors. However, lower profit margin and increased dependence are cited as the leading disadvantage of the relations. My study indicates that there is a ''critical point" which segregates subcontractors who enjoy much benefits from their subcontracting relations and those who do not. While I endorse the conclusion that subcontracting is a promising growth trajectory for small firms, such relations appear not to contribute much to their innovative capabilities. Keywords: perceived dependence